SCIENTIFIC SUBSTANTIATION OF STANDARDS RELATED TO MOTOR TRAINING OF PRIMARY GRADES STUDENTS - Ghețiu Adelina (Sport şi Societate, 2015)
This article contains scientific information on the research of motor condition of primary grades students under the example of educational institutions in rural areas of Ialoveni district, Republic of Moldova. For the first time in the last 37 years (since 1978), according to mass research of motor condition of students of primary grades, it was founded a model of tests corresponding to their motor manifestation and the control of their fulfillment will contribute to the successful development of children.